Efektifitas Penggunaan Model Pembelajaran Thinking Aloud Pairs Problem Solving (TAPPS) Terhadap Peningkatan Kemampuan Pemecahan Masalah Matematika Siswa Kelas IV Di SDN 15 Mataram - Prabarini, Ratri; Mariana, Baiq; Dewi, Nurul Kemala (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research aims to improve the mathematical problem solving abilities of fourth grade students with the Thinking Aloud Pairs Problem Solving (TAPPS) learning model. The subjects of this research were fourth grade students at SDN 15 Mataram. The action hypothesis in this research is that the use of the Thinking Aloud Pairs Problem Solving (TAPPS) model will improve mathematical problem solving abilities. This research is classroom action research with three cycles. The results of this research indicate that the Thinking Aloud Pairs Problem Solving (TAPPS) learning model can be used to improve students' mathematical problem solving abilities. This can be seen from: (1) ability to analyze problems, and (2) understanding in solving problems in mathematics is getting better from cycle to cycle. Based on the research that has been carried out and the discussion regarding the application of the Thinking Aloud Pairs Problem Solving (TAPPS) learning model to improving mathematics problem solving abilities for class IV SDN 15 Mataram, the following conclusions can be drawn: in the application of the Thinking Aloud Pairs Problem Solving (TAPPS) learning model can improve learning outcomes in the Mathematics subject material fractions for class IV students at SDN 15 Mataram. Judging from the research results in the first cycle, it shows that the class average score is 74.5, even though it has not yet reached the classical completeness that has been set, namely 80% and the classical completeness presentation obtained is 75%. Meanwhile, in cycle II there was an increase in the average class score, namely 86.75, and classical completeness by 92%.